Nanoscopic materials: size-dependent phenomena - Roduner, Emil (NBN International, 2006)
Nanotechnology has been hailed as a key technology of the 21st century. The scope of this field is huge and could have a wide influence on many aspects of life. Nanoscience; the manipulation of matter at the atomic and molecular level, and nanomaterials; materials so small that their behaviour and characteristics deviate from those of macroscopic specimens and may be predicted by scaling laws or by quantum confinement effects, are discussed this book. The book focuses on a qualitative and quantitative approach discussing all areas of nanotechnology with particular emphasis on the underlying physico-chemical and physical principles of nanoscience. Topics include electronic structure, magnetic properties, thermodynamics of size dependence and catalysis. There is also a section discussing the future potential of the field and the ethical implications of nanotechnology. The book is ideal for graduate students of chemistry and materials science and researchers new to the field of nanoscience and nanotechnology.